Strengthening Public Speaking Skills Among Student Council Leaders To Enhance Self-Confidence And Effective Organizational Communication At Islamiyah Senior High School, Tambak - Nurdiana, Defi Dachlian; Veronica, Ayuan; Suntin, Nur; Nurhaiza, Siti (PUDAK: Local Wisdom Community Journal, 2024)
Public speaking is the ability to speak or convey information to a large audience in a clear, engaging, effective, and communicative manner. This skill can help an individual become more confident in delivering information effectively, as well as influence or persuade others. This community service aims to enhance confidence and communication skills in organizational leadership for the BES management at SMA Islamiyah Tambak. The methods used include training, practice, and mentoring. The outcomes of this service show that the BES participants were able to understand strategies for public speaking, build self-confidence, and communicate calmly and effectively. Additionally, participants were able to choose and deliver positive statements when communicating with others.